KEPEMIMPINAN KHARISMATIK, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI JAMA’AH NW DI LOMBOK TIMUR - Huspiani, Huspiani; Hadiyati, Ernani; Muawanah, Umi (Universitas Hamzanwadi, 2023)
The aim of the research is to analyze and explain the influence of charismatic leadership style and organizational culture on organizational commitment of the Nahdlatul Wathan congregation in the district. East Lombok. The population in this research is all people in East Lombok who claim or declare themselves to be citizens or congregations of Nahdatul Wathan (NW). with purposive and random sampling techniques, the number of samples in this study was 211 respondents. This type of research is causal associative research which aims to analyze the relationship between one variable and other variables. The research results show: 1). Charismatic Leadership Style has a variably positive influence on Organizational Commitment, 2). And Organizational Culture has a variably positive influence on Organizational Commitment and is significant, 3.) Charismatic Leadership Style and Organizational Culture are simultaneously positive on Organizational Commitment, 4). Organizational Culture has more influence on Organizational Commitment compared to Charismatic Leadership.